The Experience of Cash Transfers in Myanmar : Lessons from a Social Protection and Poverty Reduction Perspective - Infante-Villarroel, Mariana (World Bank, Washington, DC, 2015)
Cash is an appropriate instrument to provide assistance to poor and vulnerable households in most contexts in Myanmar. Cash transfers (CTs) have the potential to help poor and vulnerable householdsmeet basic needs and encourage investments in human capital accumulation. Building on existing programs such as the stipends program and testing CTs with relatively simple design and implementation arrangements can be a viable option in the short term.